Centralised cum sub‐centralised scheme for multi‐event coverage and optimum camera activation in wireless multimedia sensor networks. Issue 6 (1st November 2015) - Priyadarshini, Sushree Bibhuprada B.; Panigrahi, Suvasini
Abstract : The major challenge in sensor networks is how to have a perfect coverage of the region to be monitored. This study reports a novel algorithm inspired by centralised cum sub‐centralised scheme that works efficiently for handling multiple events that occur simultaneously, while reducing the number of unnecessarily activated cameras so as to cover the occurring event region effectively. When any event takes place, the sensing of event occurs up to certain extent outside the exact event boundary. Hence, the cameras present beyond the boundary of event are activated unnecessarily. Since the proposed methodology avoids undesirable activation of cameras, the additional energy and power expenditure due to those cameras as well as the redundant data transmission prevailing due to them are eliminated. Results obtained from experimental evaluation reveal that the proposed methodology significantly reduces the number of unnecessarily activated cameras while providing the adequate coverage of event region for multi‐event occurrence. Further more, the reduced camera actuation with increased coverage ratio, minimised redundancy ratio, improved field of view utilisation, less energy as well as power expenditure required for camera activation obtained from the investigation justifies the effectiveness of the proposed algorithm as compared with two other approaches recently proposed in the literature.